Goodbye, sweet girl : a story of domestic violence and survival - Sundberg, Kelly, 1977- (Harper, an imprint of HarperCollinsPublishers, 2018)
Kelly Sundberg<U+2019>s husband, Caleb, was a funny, warm, supportive man and a wonderful father to their little boy Reed. He was also vengeful and violent. But Sundberg did not know that when she fell in love, and for years told herself he would get better. It took a decade for her to ultimately accept that the partnership she desired could not work with such a broken man. In her remarkable book, she offers an intimate record of the joys and terrors that accompanied her long, difficult awakening, and presents a haunting, heartbreaking glimpse into why women remain too long in dangerous relationships. To understand herself and her violent marriage, Sundberg looks to her childhood in Salmon, a small, isolated mountain community known as the most redneck town in Idaho. Like her marriage, Salmon is a place of deep contradictions, where Mormon ranchers and hippie back-to-landers live side-by-side; a place of magical beauty riven by secret brutality; a place that takes pride in its individualism and rugged self-sufficiency, yet is beholden to church and communal standards at all costs.